Generative Artificial Intelligence, meaning construction and social networks: a sociological perspective - Mattioli, Francesco (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
On the role and prospects of AI, sociology offers significant theoretical and research contributions. First of all, in the study of the processes of negotiation and construction of meaning. AI would seem to be able to reduce the degree of uncertainty in the so-called liquid society, but it could generate a complexity linked to the comparison between an algorithmic logic and certain shared ethical values. Furthermore, studies on social networks should be mentioned, which are generated by interaction systems capable of influencing individual and collective conduct, starting from the most advanced developments in media communication, today governed by AI. Thus, society, as a network, would acquire an increasingly heuristic value in the interpretation of social processes. Finally, many studies concern the role of AI in social change, both in the broader context of sustainable development, and in the face of the possibility of rebalancing the differences between rich and poor countries, and still in the study of social differentiation of generational origin.